The geotourism industry in the 21st century the origin, principles, and futuristic approach - Nikūʾī Ṣadrī, Bahrām 1973- (Apple Academic Press, 2022)
The scope and nature of geotourism in the 21st century / Bahram N. Sadry -- Historical viewpoints on the geotourism concept in the 21st century / Thomas A. Hose -- Urban geotourism in Poland / Krzysztof Gaidzik -- Mining heritage as geotourism attractions in Brazil / Antonio Liccardo, Virginio Mantesso-Neto, and Marcos Antonio Leite do Nascimento -- Geomorphosites : aesthetic landscape features or earth history heritage? / Emmanuel Reynard -- Geoheritage and geotourism in Albania / Afat Serjani -- Establishing an appropriate methodology for the management of geological heritage for geotourism development in the Azores Unesco Global Geopark / Eva Almeida Lima and Marisa Machado -- "Simply the best" : the search for the world's top geotourism destinations / Murray Gray --Interpreting mining : a case study of a coal mine exhibit / Ted T. Cable -- Geotrails / Thomas A. Hose -- Interpreting geological and mining heritage / Ross Dowling --